2021
DOI: 10.1021/acsami.1c11866
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Halide Perovskite Film-Based Neuromorphic Phototransistors for Mimicking Experience-History-Dependent Sensory Adaptation

Abstract: Sensory adaptation is an essential function for humans to live on the earth. Herein, a hybrid synaptic phototransistor based on the mixed-halide perovskite/organic semiconductor film is reported. This hybrid phototransistor achieves photosensitive performance including a high photoresponsivity over 4 × 103 A/W and an excellent specific detectivity of 2.8 × 1016 Jones. Due to the photoinduced halide-ion segregation of the mixed-halide perovskites and their slow recovery properties, the experience-history-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Furthermore, the photoinduced halide‐ion segregation of mixed‐halide perovskites was applied to fabricate CsPbBr x I 3‐x /TIPS‐based optoelectronic synaptic phototransistors for emulating the experience‐history‐dependent sensory adaptation behavior. [ 84 ] Figure 15d shows the human olfactory process to sense odorant molecules. The adaption of an intact olfactory receptor neuron indicates less neural activity can be obtained under the second stimuli when applying a pair of odor stimuli with a short time interval to the device (Figure 15e).…”
Section: Applications Of Metal Halide Perovskites‐based Optoelectroni...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the photoinduced halide‐ion segregation of mixed‐halide perovskites was applied to fabricate CsPbBr x I 3‐x /TIPS‐based optoelectronic synaptic phototransistors for emulating the experience‐history‐dependent sensory adaptation behavior. [ 84 ] Figure 15d shows the human olfactory process to sense odorant molecules. The adaption of an intact olfactory receptor neuron indicates less neural activity can be obtained under the second stimuli when applying a pair of odor stimuli with a short time interval to the device (Figure 15e).…”
Section: Applications Of Metal Halide Perovskites‐based Optoelectroni...mentioning
confidence: 99%
“…e) Adaptation of an intact olfactory receptor neuron. f) Current of the CsPbBr x I 3-x /TIPS-based phototransistor with 50 light pulse stimulations (365 nm, 20 µW cm −2 ) separated by dark-rest periods mimicking the olfactory adaptation at V DS of −1 V and V GS of 0 V. Reproduced with permission [84]. Copyright 2021, American Chemical Society.…”
mentioning
confidence: 99%
“…12,14 It gives artificial photonic synapses potential applications in wireless human-computer interaction and nextgeneration multifunctional sensors. 15 Halide perovskites have been widely applied in photonic synapse transistors as light-absorbing materials [16][17][18][19][20][21][22][23] due to their excellent light absorption properties, high charge separation efficiency, tunable bandgap, and stability when stored in solution. 24,25 Recent studies have shown the integration of inorganic perovskites in optoelectronic devices with good atmospheric stability and extremely low response energies.…”
Section: Introductionmentioning
confidence: 99%
“…There is enough time and space to assemble molecules, and small molecules can be orderly stacked into large oriented crystals, forming organic semiconductor films with fewer grain boundary densities and defect sites. 9 Many extensive types of research on the solution preparation processes of organic semiconductors including spin-coating, 10,11 drop-coating, [12][13][14] slot-coating, 15 blade coating, 16 dip-coating, 16 spray coating, 17 solution shear method, 18 LB (Langmuir Blodgett) method, 19 droplet fixation method, 20 solution steam annealing method, 20 capillary gradient method 21 and template-assisted methods 22 have been conducted. A solution-processible fabrication strategy for patterned organic thin film transistors has many advantages, including low production costs, and is expected to become a reliable process for preparing array devices.…”
Section: Introductionmentioning
confidence: 99%